Implementation Of Character Education Values In The Syi'ir Ngudi Susilo Manuscript At TPQ Al Muktamar - Rahmat, Nur; Mukhlisin, Mukhlisin; Wangi, Nisaul Barokati Seliro; Wahyono, Imam; Azis, Abd. (STAI Miftahul Ula Nganjuk, 2024)
This study aims to (1) describe the implementation of the learning process of the Syi'ir Ngudi Susilo manuscript at TPQ Al Muktamar, (2) identify the character values embedded in the manuscript, and (3) examine the application of character education values derived from the manuscript. A qualitative descriptive approach with a case study methodology was employed, conducted at TPQ Al Muktamar. Data were collected through interviews, observations, and documentation. The findings of this study reveal that the learning process of the Syi'ir Ngudi Susilo manuscript at TPQ Al Muktamar is effective in promoting character development among students. The manuscript incorporates significant character values, such as discipline, respect, patience, and devotion, which are essential in shaping students' moral and ethical behavior. The character values embedded within the manuscript have been instrumental in fostering better character development among students, influencing both their academic and personal lives. Additionally, the application of these values through the learning process at TPQ Al Muktamar has successfully instilled positive habits and motivated students to apply these values in their daily routines. In conclusion, the Syi'ir Ngudi Susilo manuscript has proven to be an effective tool for character education at TPQ Al Muktamar, as it not only educates students about religious teachings but also shapes their moral character. This study highlights the importance of integrating character education into religious learning, which can play a significant role in cultivating a well-rounded, ethically driven generation.